PRKRA Localizes to Nuage Structures and the Ectoplasmic Specialization and Tubulobulbar Complexes in Rat and Mouse Testis. (25th February 2014) - Suzuki, Junya; Yokota, Sadaki
Abstract : The cytoplasmic RNA-induced silencing complex (RISC) contains dsRNA binding proteins, including PRKRA, TRBP, and Dicer. RISC localizes to P-bodies. The nuage of the spermatogenic cells has function similar to the P-bodies. We study whether PRKRA localizes to nuage of spermatogenic cells of rat and mouse. PRKRA localized to four types of nuage structures, including aggregates of 60–90 nm particles, irregularly-shaped perinuclear granules, and intermitochondrial cement of pachytene spermatocytes, and chromatoid bodies of round spermatids. In addition, PRKRA is associated with dense material surrounding tubulobulbar complexes and with the ectoplasmic specialization. The results suggest that PRKRA functions in the nuage as an element of RNA silencing system and plays unknown role in the ectoplasmic specialization and at the tubulobulbar complexes of Sertoli cells attaching the head of late spermatids.